Phosphatidylinositol-stimulated phosphorylation of an inhibitory subunit of cGMP phosphodiesterase in vertebrate rod photoreceptors. - Hayashi, F (1991)
An inhibitory subunit (P gamma) of cGMP phosphodiesterase from vertebrate rod photoreceptors (frog, toad, and bovine) was phosphorylated by cytosolic protein kinase(s) derived from intact frog rod outer segments. The phosphorylation of frog P gamma was stimulated by phosphatidylinositol but not by cAMP or cGMP. One- and two-dimensional gel electrophoresis revealed that 70-80% of P gamma was phosphorylated with 1 mol of phosphate per frog P gamma under optimal conditions. A peptide that derived from an active domain of bovine P gamma was also phosphorylated. Phosphorylation of frog P gamma was inhibited by addition of the peptide to the reaction mixture. Phosphorylation of frog P gamma was also inhibited by addition of transducin subunits or active (P gamma-less) cGMP phosphodiesterase. Okadaic acid, on the other hand, enhanced P gamma phosphorylation, suggesting the presence of protein phosphatase(s) in the cytosolic fraction. These data suggest another mechanism for the regulation of cGMP phosphodiesterase in vertebrate rod photoreceptors.